Comparative assessment of yield, oil content and fatty acid composition of spiny and non-spiny safflowers - Sajid Muhammad; Munir Hassan; Rasul Fahd; Hayat Muhammad Abu Bakar (Oilseeds and fats, crops and lipids)
Safflower (Carthamus tinctorius L.) is one of the edible oilseeds crops which is neglected due to its spiny nature that poses difficulties in field operations; however, this problem can be sorted out by introducing non-spiny safflower cultivars. Hence, a 2-year study (2020–2021 and 2021–2022) was planned to assess the production potential of spiny (5 accessions) and non-spiny (5 accessions) safflower germplasm and an experiment was laid out using randomized completed block design (RCBD) under semiarid conditions of Faisalabad (Pakistan). Agronomic and oil traits were targeted during study. In 2021, non-spiny safflower accession PI-198990 gave the highest seed yield and oil percentage as compared to spiny safflower. However, the highest linoleic concentration was noted in spiny PI-199829 accession whereas the greatest oleic acid percentage was determined in non-spiny PI-235660 accession. Principal component analysis unveiled two components accounting for 39.5% and 25.7% of total variation. Biplot graph indicated that seed oil content, seed yield and 1000-seed weight had the highest correlation in the 2nd group while in the 3rd group plant height, days to maturity and oleic acid were correlated. These targeted characters can be considered as suitable index for selection of safflower elite accessions for semi-arid conditions. In general, non-spiny safflower accession responded 19%, 4.3%,10.7%, 21.6%, 6.2% and 77.9% greater in plant height, number of branches, number of heads (capitula), 1000-seed weight, seed yield and oleic acid respectively. From the data of this 2-year studies, we concluded that spiny safflower accessions exhibited 1.2% and 16.3% more oil and linoleic acid content respectively.